Cyanobacterial Blooms and the Presence of Cyanotoxins in the Brazilian Amazon - Maria Paula Cruz Schneider; Elane Cunha; Lucas Silva; James Leão; Vanessa Costa Tavares; Eliane Brabo de Sousa; Silvia Faustino (Toxins, 2025)
The records of blooms and cyanotoxins in the Brazilian Legal Amazon are scarce and do not represent the reality observed in recent years when there was an increase in notifications and studies carried out in this region. In this article, we carefully analyzed 48 studies to identify the locations where the blooms occurred, the most frequent species, and the tests performed to detect cyanotoxins within the territory of the Brazilian Legal Amazon. The analyzed studies identified approximately 145 taxa of cyanobacteria, and the most frequent species belong to the genera Microcystis and Planktothrix. The most frequently detected cyanotoxin was microcystin, and, in some locations, even with a low cell density, there was the production of toxins. In most cases, Microcystis and Dolichospermum were the major genera associated with blooms and toxin production. The state of Pará had the highest number of records of toxin-producing cyanobacteria, including records of seasonal events, while Acre had no records. This work contributes to our knowledge of the geographic distribution and occurrence of cyanobacteria and cyanotoxins in the Brazilian Amazon and proposes new strategies for improving the monitoring of cyanotoxins in the Amazon region.